2018
DOI: 10.1158/1078-0432.ccr-17-1533
|View full text |Cite
|
Sign up to set email alerts
|

PTEN Is Fundamental for Elimination of Leukemia Stem Cells Mediated by GSK126 Targeting EZH2 in Chronic Myelogenous Leukemia

Abstract: Leukemia stem cells (LSCs) are an important source of tyrosine kinase inhibitor resistance and disease relapse in patients with chronic myelogenous leukemia (CML). Targeting LSCs may be an attractive strategy to override this thorny problem. Given that was overexpressed in primary CML CD34 cells, our purpose in this study was to evaluate the effects of targeting EZH2 on CML LSCs and clarify its underlying mechanism. Human primary CML CD34 cells and retrovirally -driven CML mouse models were employed to evaluat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 44 publications
0
19
0
Order By: Relevance
“…Cytosolic fraction for cytochrome c detection was prepared using the digitonin extraction buffer (10 mmol/L PIPES, 0.015% digitonin, 300 mmol/L sucrose, 100 mmol/L NaCl, 3 mmol/L MgCl 2 , 5 mmol/L EDTA, and 1 mmo/L phenylmethylsulfonyl fluroride) [30]. Briefly, cell pellets were suspended in digitonin extraction buffer on ice for 10 min.…”
Section: Methodsmentioning
confidence: 99%
“…Cytosolic fraction for cytochrome c detection was prepared using the digitonin extraction buffer (10 mmol/L PIPES, 0.015% digitonin, 300 mmol/L sucrose, 100 mmol/L NaCl, 3 mmol/L MgCl 2 , 5 mmol/L EDTA, and 1 mmo/L phenylmethylsulfonyl fluroride) [30]. Briefly, cell pellets were suspended in digitonin extraction buffer on ice for 10 min.…”
Section: Methodsmentioning
confidence: 99%
“…To further evaluate the oncogenic role of PCAT6, we performed a correlation analysis to explore the relationship between PCAT6 and stemness. However, we found that the expression of PCAT6 showed a significantly negative association with CD34 , a marker of stemness (Figure A) (r = −0.12, P = 1.97 × 10 −2 ) . Additionally, no relationship was observed between PCAT6 and mRNAsi (mRNA expression‐based stemness index)/mDNAsi (DNA methylation‐based stemness index) (r = −0.07, P = 1.76 × 10 −1 ; r = 0.03, P = 5.71 × 10 −1 ; Figure B).…”
Section: Resultsmentioning
confidence: 90%
“…PCAT‐1 has been reported to silence gene expression by recruiting EZH2, a vital catalytic subunit of polycomb repressive complex 2 complex (PRC2), to the specific genome sites of target genes . Moreover, PTEN could be suppressed by EZH2 through the enrichment of H3K27me3 on its promoter region in various cancers . Thus, we wondered whether PCAT‐1 epigenetically repressed PTEN through EZH2 in GC.…”
Section: Resultsmentioning
confidence: 99%